EQUITY PRINCIPLE AS TRUST CONTRACT PRINCIPLE IN BANKING AND ITS IMPACT TO NATIONAL CONTRACT LAW RENEWAL - Tri Handayani; Lastuti Abubakar (University of Sumatera Utara, 2017)
National bank industry need a strong legal principles to run its function as intermediary institution in supporting national development and global access in order to be able to compete in welcoming ASEAN Banking Integration Framework (ABIF) in 2020. To anticipate that, Banking develop banking services based on contract. One of many, is Bank Indonesia which has issued PBI No. 14/17/PBI/2012 regarding deposit and managing (Trust) which then revised with POJK No: 25/POJK.03/2016 regarding revision of POJK No: 27/POJK.03/2015, which brought forward equity principle. This activity brings impact in contract law development. In its implementation, equity principle was troubled with the difference its definition or application in Indonesia and other countries with common law legal system. The issues to be discussed are (1) How is the implementation of equity principle in trust agreement to push the development of national banking? (2) how is the urgency of contract law system renewal in accommodating trust agreement? Based on the previous research, the result is: there is difference in definition and scope of equity in its implementation based on Indonesian contract law. The implementation of equity principle hasn’t been performed optimally, remembering Indonesian legal system which doesn’t recognize dual ownership which is the essence in trust agreement. Because of this, certain effort is necessary to implement equity principle concretely. It is time for Indonesia to renew its contract law to be able to compete the vast development of banking activity or other rapidly developing business.